Combat trauma: imaginaries of war and citizenship in post-9/11 America - Abu El-Haj, Nadia (London, UK: New York, USA: Verso, 2022)
Americans have long been asked to support the troops and care for veterans' psychological wounds. Who, though, does this injunction serve? As acclaimed scholar Nadia Abu El-Haj argues here, in the American public's imagination, the traumatized soldier stands in for destructive wars abroad, with decisive ramifications in the post-9/11 era. Across the political spectrum the language of soldier trauma is used to discuss American warfare, producing a narrative in which traumatized soldiers are the only acknowledged casualties of war, while those killed by American firepower are largely sidelined and forgotten. In this wide-ranging and fascinating study of the meshing of medicine, science, and politics, Abu El-Haj explores the concept of post-traumatic stress disorder and the history of its medical diagnosis. While antiwar Vietnam War veterans sought to address their psychological pain even as they maintained full awareness of their guilt and responsibility for perpetrating atrocities on the killing fields of Vietnam, by the 1980s, a peculiar convergence of feminist activism against sexual violence and Reagan's right-wing "war on crime" transformed the idea of PTSD into a condition of victimhood. In so doing, the meaning of Vietnam veterans' trauma would also shift, moving away from a political space of reckoning with guilt and complicity to one that cast them as blameless victims of a hostile public upon their return home. This is how, in the post-9/11 era of the Wars on Terror, the injunction to "support our troops," came to both sustain US militarism and also shields American civilians from the reality of wars fought ostensibly in their name. In this compelling and crucial account, Nadia Abu El-Haj challenges us to think anew about the devastations of the post-9/11 era.
I. From agent to victim: Psychiatry as radical critique: "Post-Vietnam Syndrome" -- The Politics of victimization: feminism, the Victims of Crime Movement, and reconstructing the War in Vietnam -- II. 9/11 and its aftermath: Soldier's trauma, revisited -- The politics of moral inquiry -- III. Consripting citizens: Caring for militarism -- The (American) civilian -- Epilogue.
Includes bibliographical references and index.
Keywords: 1900-2099; Veterans -- United States -- Psychology; Post-traumatic stress disorder -- United States; Veterans -- Mental health -- United States; Combat -- Psychological aspects; Veterans -- United States -- Social conditions; Post-traumatic stress disorder; Veterans -- Psychology; Veterans -- Social conditions; Stress; Violence; United States -- History, Military -- 20th century; United States -- History, Military -- 21st century; United States; Military history